Characterization of Human Spinal Cord Stem Cells to Improve the Translation of Cell Therapies for Spinal Cord Injury - Galuta, Ahmad (Université d'Ottawa / University of Ottawa, 2023)
Stem cell treatments for spinal cord injury (SCI) are effective in pre-clinical animal model research but not yet for humans. Two promising stem cell repair strategies involve (1) endogenous neural stem/progenitor cells (NSPCs) and (2) induced pluripotent stem cells (iPSCs). Delineating species differences in spinal cord NSPC biology is essential to inform human SCI endogenous regeneration and repair. Understanding the phenotypic differences between iPSC-derived NSPCs and primary spinal cord NSPCs would also improve the clinical application of iPSC-derived NSPC therapy in human SCI. To directly compare the molecular and functional attributes of spinal cord NSPCs between humans and animal models of SCI, we designed an in vitro model that allows the characterization of primary human, pig, and rat NSPCs under identical conditions. We found an enrichment of transcription factors in NSPCs of either species that may underlie their differentiation and proliferation potentials. Specifically, human NSPCs are neurogenic, whereas pig and rat NSPCs are gliogenic. Also, the proliferation rate of human and pig NSPCs is less than rat NSPCs. Subsequently, we expanded our in vitro model to examine the responses of NSPCs to inflammation and regenerative factors. Surprisingly, inflammation had induced glial scarring mechanisms from pig and rat NSPCs but potentiated neurogenesis of human NSPCs. We also found species-specific responses to regenerative factors that depend on the type of factor used, concentration, and duration of treatment. To assess the extent that iPSC-derived NSPCs phenocopy primary spinal cord NSPCs, we created iPSC-derived NSPCs with a previously reported brain or spinal cord phenotype and directly compared them with isogenic primary NSPCs. We found that iPSC-derived NSPCs exhibit an earlier developmental stage and a greater proliferation rate. We also found that primary NSPCs possess a unique differentiation potential and regional polarity along the rostral-caudal and dorsoventral axes. In summary, we discovered that species differences in NSPC biology exist between human and animal primary spinal cord NSPCs and that iPSC-derived NSPCs do not recapitulate the transcriptional nor functional attributes of primary spinal cord NSPCs. This thesis highlights the translational gap between pre-clinical research and the clinical application of stem cell treatments that target endogenous NSPCs or transplant iPSC-derived NSPCs.
Keywords: Spinal Cord Injury; Neural Stem Cells; Regenerative Medicine; Induced Pluripotent Stem Cells; Translational Research